A Redox‐Active Bis(ferrocenyl)germylene and Its Reactivity. Issue 2 (11th December 2017) - Suzuki, Yuko; Sasamori, Takahiro; Guo, Jing‐Dong; Tokitoh, Norihiro
Abstract: Bis(ferrocenyl)germylene Fc*2 Ge: [2 ; Fc*=2, 5‐bis(3, 5‐di‐ tert ‐butylphenyl)‐1‐ferrocenyl] was isolated in the form of red crystals from the reaction of the sterically demanding ferrocenyl lithium dimer (Fc*Li)2 and GeI2 . Bis(ferrocenyl)germylene2 exhibits extraordinary thermal stability in hydrocarbon solution and the solid state, as well as stable redox behavior. Moreover, it undergoes a ligand‐redistribution reaction with GeCl2 ⋅(dioxane) to afford the corresponding chlorogermylene, which was isolated upon coordination with PBu3 . Abstract : A bis(ferrocenyl)germylene compound was obtained from the reaction of a sterically demanding ferrocenyl lithium dimer with GeI2 . The compound exhibits exceptionally high thermal stability in solution and the solid state, as well as stable redox properties. Moreover, it undergoes a ligand‐redistribution reaction with GeCl2 ⋅(dioxane) to afford the corresponding chlorogermylene, which was isolated upon coordination with PBu3 .